Analysis of antibiotic resistance in Gram-negative bacilli in wild and exotic healthy birds in Brazil: A warning sign - Ramos, Carolina Aparecida; Ferreira, Joseane Cristina; Ballaben, Anelise Stella [UNESP]; Filho, Rafael Antonio Casarin Penha [UNESP]; Darini, Ana Lúcia da Costa (Elsevier, 2024)
Bacterial antibiotic resistance is a public health problem affecting humans and animals. This study focuses on identifying Gram-negative bacilli (GNB) (MALDI-TOF MS and Klebsiella MALDI TypeR) resistant to antimicrobials in freshly emitted feces of healthy captive and rescued wild birds from a zoo in Brazil. Birds from the zoo and rescued from sixteen different orders were investigated. Resistant bacteria from feces were selected (MacConkey agar with 2 μg/mL cefotaxime). Genomic similarity and plasmid were investigated by Pulsed-Field Gel Electrophoresis of XbaI fragments (XbaI-PFGE) and S1-PFGE. Polymerase Chain Reaction (PCR) was performed to search for beta-lactamase genes. From 80 birds included, 26 from the zoo (50 %) and 18 rescued wild birds (64 %) presented cefotaxime-resistant GNB. E. coli and Klebsiella spp were the most prevalent species. Among 65 isolates from the zoo and rescued wild birds, 75 % were considered multidrug-resistant (MDR). The majority of the isolates were extended-spectrum beta-lactamases (ESBL) producing and resistant to enrofloxacin. blaCTX-M-GROUP-1, blaTEM, and blaSHV were the most detected genes, and blaKPC was detected in K. pneumoniae complex. According to genomic similarity results, some identical profiles were found in birds with no known contact among the zoo or rescued birds. Several isolates carried one to three plasmids (15–350 kb). The presence of multidrug-resistant (MDR) isolates from healthy captive and wild birds brings novel data on the dissemination of these elements to the environment.
Keywords: bla genes; Enterobacterales; ESBL; One Health; Plasmids